Dampak Tekanan Pekerjaan dan Lingkungan Kerja Toxic Terhadap Kinerja Karyawan - Jasmine Balqist; Asep Muhamad Ramdan; Resa Nurmala (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2023)
The purpose of this study was to determine the impact of job stress and toxic work environment on employee performance at PT Tirta Jaya Mandiri Regional Drinking Water Company. The methods used in this research are descriptive and associative with a quantitative approach. The sampling technique in this study used saturated sampling, the samples taken in this study were 30 employees. The data analysis technique uses validity and reliability tests, classical assumption tests, multiple linear regression including correlation coefficients, determination, research hypothesis submission. The results of the study using the coefficient of determination test show that job stress and the work environment affect employee performance by 63% while the remaining 37% is influenced by other factors outside of the study. Based on the multiple correlation coefficient test, it can be seen from the R value of 0.794, which means that there is a fairly high relationship between job pressure and the work environment on employee performance. The results of the F test, namely the value of Fcount 7.371> F table 3.354, show that Fcount is greater than Ftable. Job pressure and work environment variables have a positive and significant effect on employee performance.